2020
DOI: 10.1097/md.0000000000019050
|View full text |Cite
|
Sign up to set email alerts
|

Maximal muscle strength and body composition are associated with bone mineral density in chinese adult males

Abstract: The relationship between maximal muscle strength (MMS) and bone mineral density (BMD) in males remains unclear. Therefore, the aim of this cross-sectional study was to investigate the association of MMS, using 3 fundamental compound exercises, and body composition with BMD in Chinese male adults. One hundred forty-seven Chinese male adults aged 20 to 47 years were recruited. Total and regional BMD and body composition were measured using dual-energy X-ray absorptiometry. Measurements of MMS included bench pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Most studies have not seen further stratification analysis of whole-body muscles. However, it is found that there is a positive correlation between muscle and BMD [ 46 ]. Lower limb muscle mass is more conducive to the prevention of osteoporosis than body muscle and upper limb muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have not seen further stratification analysis of whole-body muscles. However, it is found that there is a positive correlation between muscle and BMD [ 46 ]. Lower limb muscle mass is more conducive to the prevention of osteoporosis than body muscle and upper limb muscle.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the interactions between muscle mass and function (e.g., strength and power) and bone health in Chinese young adults, particularly women, are understudied. Recently, both muscle strength and lean mass were reported to be positively correlated with spine, hip, and total body aBMD in Chinese men aged 20-47 years [25]. In contrast, muscle strength assessed by grip strength but not by muscle mass was related to bone status in an elderly cohort of Chinese men and women with higher grip strength being associated with a lower risk of osteoporosis [26].…”
Section: Discussionmentioning
confidence: 99%
“…At all ages, a significant correlation was shown between muscle mass, muscle strength, and bone density (Sutter et al, 2019;Chen F. et al, 2020;Lopes et al, 2021). Irisin, a myokine induced during exercise, is thought to be an osteoprotective factor that acts on bone and affects bone density.…”
Section: The E Ects Of Irisin On Osteoarthritis Irisin and Bone Miner...mentioning
confidence: 99%